Pengaruh Persepsi Profesi Guru dan Kesejahteraan Guru terhadap Minat Menjadi Guru Pada Mahasiswa Pendidikan Administrasi Perkantoran - Sabrina Aisya Putri; Christian Wiradendi Wolor; Darma Rika Swaramarinda (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2025)
Interest is when a person feels attracted to something or an activity without any coercion. Higher education has an education study program which basically aims to produce prospective teachers or educators in the future. However, nowadays it is often found that students of Education study programs are less interested in becoming teachers. This can be influenced by various factors, including perceptions of the teaching profession and teacher welfare. This study aims to determine the effect of perceptions of the teaching profession and teacher welfare on students' interest in becoming teachers. This research uses quantitative methods. Data were obtained from a sample of 63 people with probability sampling technique. The analysis technique used was the analysis requirement test, classical assumption test, and hypothesis testing using SPSS 26. The results showed that: (1) There is a positive and significant influence between perceptions of the teaching profession and interest in becoming a teacher; (2) There is no influence between perceptions of teacher welfare and interest in becoming a teacher; (3) There is a positive and significant influence between perceptions of the teaching profession and perceptions of teacher welfare with interest in becoming a teacher.